2011
DOI: 10.1038/ismej.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

The oral metagenome in health and disease

Abstract: The oral cavity of humans is inhabited by hundreds of bacterial species and some of them have a key role in the development of oral diseases, mainly dental caries and periodontitis. We describe for the first time the metagenome of the human oral cavity under health and diseased conditions, with a focus on supragingival dental plaque and cavities. Direct pyrosequencing of eight samples with different oral-health status produced 1 Gbp of sequence without the biases imposed by PCR or cloning. These data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
403
3
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(443 citation statements)
references
References 52 publications
27
403
3
10
Order By: Relevance
“…The two acid-resistant genes obtained in this study were aligned with sequences from two common cariogenic genera, Actinomyces and Haemophilus [30], which represent two of seven dominant cariogenic phyla (Actinobacteria and Proteobacteria) [31]. Bioinformatics analysis found that the ORF in pSL-2–41 encodes two domains (the malic and Malic_M domains) that form the N-terminal region of the malate dehydrogenase protein, but the acid-resistance assay indicated that this fragment is sufficient to allow E. coli to survive in this hostile environment.…”
Section: Discussionmentioning
confidence: 99%
“…The two acid-resistant genes obtained in this study were aligned with sequences from two common cariogenic genera, Actinomyces and Haemophilus [30], which represent two of seven dominant cariogenic phyla (Actinobacteria and Proteobacteria) [31]. Bioinformatics analysis found that the ORF in pSL-2–41 encodes two domains (the malic and Malic_M domains) that form the N-terminal region of the malate dehydrogenase protein, but the acid-resistance assay indicated that this fragment is sufficient to allow E. coli to survive in this hostile environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown differences in microbial gene expression based on sample site within the oral cavity [13] between health and periodontitis [14] and dental caries [15,16]. Microbial gene expression activity in dentin can differ markedly from that in enamel and closer to the tooth surface [16].…”
Section: Introductionmentioning
confidence: 99%
“…Atopobium has been reported to be present in varying stages of the disease including early colonization of dental tissues. [2,[22][23][24] Actinomyces is an acidogenic bacteria with 8.3% of total population from phylum Actinobacteria. Similar study have shown that microflora of clinically sound enamel surfaces contains mainly non-mutans Streptococci and Actinomyces, in which acidification is mild and infrequent.…”
Section: Discussionmentioning
confidence: 99%